2(3x²-1)-(2x-1)(x+2)=
(a-2)²=
(2x-3y)²=
(3ac²-3a²c)²=
(3a-b)²=
(ax-5a)²=
(0,2b²-20)²=
(¹₂a do potęgi n - b do potegi n)²=
(3ax-5by)²=
(-⅓ax²-6)²=
(y+1)²=
(2x+4)²=
(3x²+2x)²=
(x do potegi n +1)²=
(3xy+⅔)²=
(0,5a²b+10c²)²=
(3 do potegi n +2x)²=
(ax+5by)²=
(½am + ⅓bn)²=
(4x²+3y²)²=

PROSZĘ UŻYWAĆ ZNAKÓW MATEMATYCZNYCH
Z GÓRY DZIĘKUJĘ :)

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-03T13:12:27+01:00
2(3x²-1)-(2x-1)(x+2)= 6x²-2- (2x²+4x-x-2) = 6x² -2-2x²-4x+x+2 =
= 4x²-3x

(a-2)²=a²-4a+4
(2x-3y)²= 4x²-18xy+9y²
(3ac²-3a²c)²=9a²c⁴ -18a³c³ +9a⁴c²
(3a-b)²= 9a²-6ab+b²
(ax-5a)²= a²x² - 10a²x+28a²
(0,2b²-20)²=0,04b⁴ -8b² +400
(¹₂a do potęgi n - b do potegi n)²= ¼a (do potęgi 2n) - a (do potęgi n) *b (do potęgi n) + b (do potęgi 2n)
(3ax-5by)²= 9a²x² -30axby + 25b²y²
(-⅓ax²-6)²= ¹/₉ a²x⁴ + 4ax² +36
(y+1)²= y²+2y+1
(2x+4)²= 4x²+16x+16
(3x²+2x)² = 9x⁴ +12x³+4x²
(x do potegi n +1)²= x (do potęgi 2n) +2x (do potęgi n) +1
(3xy+⅔)²= 9x²y² +4xy + ⁴/₉
(0,5a²b+10c²)²= 0,25 a⁴b² + 10a²bc² + 100c⁴
(3 y do potegi n +2x)²= 9 y(do potęgi 2n) + 12xy (do potęgi n) + 4x²
(ax+5by)²= a²x² +10axby + 25b²y²
(½am + ⅓bn)²= ¼a²m² + ⅓ ambn + ¹/₉ b²n²
(4x²+3y²)²= 16x⁴+24x²y²+9y⁴